Analisis Kinerja Keuangan Studi Kasus Pada Pt. X Periode Tahun 2014 Sampai 2016 - Rina Indah Hariyati (Universitas Tarumanagara, 2019)
This research aims to determine the ability of financial performance at X Company for the period of 2014 until 2016, where the analysis used is the ratio of liquidity, solvability ratio, activity ratio and profitability ratio. This study uses financial report data in the form of balance sheet and income statement with the period of 31 December 2014 until 31 December 2016. The method of analysis used for this discussion is evaluative descriptive analysis by calculating the company's financial ratios during 2014-2016 by using ratio analysis method that includes: Liquidity ratio represented by current ratio, quick ratio and cash ratio. Solvability ratios are represented by debt to total assets ratio (DAR) and debt to equity ratio (DER). The activity ratio is represented by total asset turnover (TATO), receivable turnover (RTO), and inventory turnover (ITO). Profitability ratio is represented by gross profit margin, net profit margin, return on investment (ROI) and return on equity (ROE). The conclusion of this research is that liquidity ratio measured by current ratio, quick ratio and cash ratio is good and liquid. Solvability ratio measured by DAR ratio and DER ratio is declared good and efficiently. Activity ratio as measured by RTO and ITO stated already good and efficiently, but TATO is not good and not efficiently. While profitability ratio measured with gross profit margin, net profit margin, return on investment (ROI) and return on equity (ROE) are declared good and efficient. With the calculation of liquidity ratio, solvability ratio, activity ratio and profitability ratio is expected to be useful as information before making a decision related to the X Company.